The Influence of Different Acidic Conditions on the Plant Growth-Promoting Rhizobacteria Activity of Phosphate Solubilizing Bacteria - Fitriatin, Betty Natalie; Fauziah, Detty Asna; Hindersah, Reginawanti; Simarmata, Tualar (KnE Life Sciences, 2022)
The acidity of the soil influences the amount of phosphorus available in the soil; acidic soils have low phosphorus availability. The use of phosphorus solubilizing bacteria improves phosphorus availability in acidic soils. The production of dissolved phosphorus and organic acids is one of the functions of the plant growth-promoting rhizobacteria (PGPR) activity of phosphorus solubilizing bacteria. The purpose of this study was to examine how acidity affects the organic acid production and dissolved phosphorus levels of phosphate solubilizing bacteria. Experiments were carried out in the Laboratory of Soil Biology, Department of Soil and Land Resources, Faculty of Agriculture, Universitas Padjadjaran. Two isolates of PGPR (Burkholderia sp. strain WK 11 and Burkholderia sp. strain MQ-14W) were used in this study, both of which were isolated from an acidic soil-ecosystem. pH 4.5, normal pH (7) and 10.5 were the levels of acidity. The results revealed that the acidity of the water had an effect on the amount of dissolved phosphorus and the amount of organic acid produced by the phosphate solubilizing bacteria. PSB produced more organic acid (lactic, citric, oxalic, and tartaric acid) and dissolved phosphorus at pH 4.5 than at pH 7 or pH 10.5. Keywords: Acidity, Burkholderia, organic acid, PGPR, solubilizing P